2017
DOI: 10.2528/pierm17070603
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Image Segmentation Method in Inverse Scattering for Brain Tumour Detection

Abstract: Abstract-This paper presents a microwave imaging for brain tumour detection utilizing ForwardBackward Time-Stepping (FBTS) inverse scattering technique. This technique is applied to solve electromagnetic scattered signals. It is proven that this technique is able to detect the presence of tumour in the breast. The application is now extended to brain imaging. Two types of results are presented in this paper; FBTS and FBTS integrated with image segmentation as a pre-processing step to form a focusing reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…As in the frequency domain case, the relative permittivity at the j th grid cell was changed 10% to ensure linearity. The Jacobian matrix was calculated using (48) and repeating the simulations for M grid cells. Then, the functional derivative was obtained using (51).…”
Section: Time Domain Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the frequency domain case, the relative permittivity at the j th grid cell was changed 10% to ensure linearity. The Jacobian matrix was calculated using (48) and repeating the simulations for M grid cells. Then, the functional derivative was obtained using (51).…”
Section: Time Domain Simulationsmentioning
confidence: 99%
“…It has found widespread use in many fields, including seismology, 18 ultrasound imaging, 19 blood flow and clotting, 20,21 diffuse optical tomography, [22][23][24] geophysics, 25 photonics, 26 and high-frequency structure analysis. 27 Microwave imaging also takes advantage of the adjoint method, which is frequently favored in both frequency domain [28][29][30][31][32][33][34][35][36][37][38][39][40][41] and time domain [42][43][44][45][46][47][48][49][50] imaging algorithms resulting in diverse formulations.…”
mentioning
confidence: 99%
“…Another concrete comparative study was presented by Mahmood et al [5], who demonstrated that MWT image segmentation is even capable of ameliorating the accuracy of image reconstruction using several automated segmentation methods. Joseph et al [24] integrated image segmentation with their inverse scattering algorithm called Forward-Backward Time-Stepping (FBTS) to apply on microwave imaging for brain tumors. From the retrospective work, we determine to deploy two well-known approaches as pre-study to support our methodology.…”
Section: Related Workmentioning
confidence: 99%
“…The time domain technique has the ability to reconstruct an accurate profile of electrical properties as in the FBTS technique, compared to frequency domain based technique. Thus, the FBTS technique has been used for the detection of breast cancer [6,7,35], tumors in the lung [36], and tumors in the brain [37]. Following the advancement of FBTS, filters such as Elliptic filter [38] and Chebyshev filter [39] are incorporated to solve the non-linearity problem.…”
Section: Introductionmentioning
confidence: 99%